Trends in the evolution of subsidies per hectar and per livestock unit, by classes of economic dimension of agricultural holdings, in Romania and some European countries, for the period 2007-2018 - Diana Maria Ilie; Rozi Berevoianu; Raluca-Alexandra Rădoi; Manea Drăghici (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
Agricultural subsidies are an important strategy of the European Union, for improving farm incomes, economic consolidation of the agricultural sector, raising living standards and thus ensuring food security. This paper tries to answer at two questions. First, if there were significant changes between 2007-2013 and 2014-2018, of the indicators: direct payments for crop production per hectare of agricultural land and direct payments on UVM (Large Cow Unit), as direct indicators and the share of direct payments in the product of the farm and the gross product per UAM (Annual unit of work) as impact indicators. Second, if the differences of these indicators compared to the European Union average deviate significantly. The statistical indicators used were: average, standard deviation.
Keywords: H23; O38; Q18; 330; subsidy; economic size of agricultural holdings; test t